Esophageal Diseases Evaluation and Treatment - Fisichella, P. Marco; Allaix, Marco E.; Morino, Mario; Patti, Marco G. (Springer International Publishing : Imprint: Springer, 2014)
Esophageal Diseases: Evaluation and Treatment is a concise and easy-to-read manual which explores the pathophysiology, diagnostic evaluation, treatment and strategies for avoiding and managing esophageal diseases.  Simple operative approaches are explained, relevant technical considerations are given, and management strategies of the disease process are described in each chapter for better understanding. Written by world class international esophageal surgeons and gastroenterologists, Esophageal Diseases: Evaluation and Treatment is a thorough handbook for surgeons and gastroenterologists in residence and training which aims to help with avoiding and managing the entire spectrum of esophageal diseases.